2022
DOI: 10.1002/nbm.4700
|View full text |Cite
|
Sign up to set email alerts
|

Efficient phase‐cycling strategy for high‐resolution 3D gradient‐echo quantitative parameter mapping

Abstract: Magnetization‐prepared (MP) gradient‐echo (GRE) sequences suffer from signal contaminations from T1 recovery during the readout train, which can be eliminated by paired RF phase cycling (PC) at the cost of doubling the scan time. The objective of this study was to develop and validate a novel unpaired PC strategy to eliminate the time penalty for high‐resolution quantitative parameter mapping in 3D MP‐GRE sequences. Based on the observation that the contaminating T1 recovery signal along the GRE readout train … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…To reduce the T 1 contamination that affects the precision of cartilage T 1ρ mapping, MAPSS required essentially two acquisitions with the same TSLs, one regular and the other with phase cycling. Peng et al 71 demonstrated that a new complex‐valued curve‐fitting model could solve the issue of T 1 contamination and acquisition time could be reduced. In the study by Han et al, 72 it was shown that MAPSS could be used efficiently to directly measure R 2 – R 1ρ maps of knee cartilage without having to acquire data to produce T 2 and T 1ρ maps.…”
Section: Emerging Methods For Quantitative Mri For Cartilagementioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the T 1 contamination that affects the precision of cartilage T 1ρ mapping, MAPSS required essentially two acquisitions with the same TSLs, one regular and the other with phase cycling. Peng et al 71 demonstrated that a new complex‐valued curve‐fitting model could solve the issue of T 1 contamination and acquisition time could be reduced. In the study by Han et al, 72 it was shown that MAPSS could be used efficiently to directly measure R 2 – R 1ρ maps of knee cartilage without having to acquire data to produce T 2 and T 1ρ maps.…”
Section: Emerging Methods For Quantitative Mri For Cartilagementioning
confidence: 99%
“…70 Efficient use of phase-cycling acquisitions in magnetization-prepared angle-modulated partitioned k-space spoiled GRE snapshots (MAPSS) sequences was proposed. 71 To reduce the T 1 contamination that affects the precision of cartilage T 1ρ mapping, MAPSS required essentially two acquisitions with the same TSLs, one regular and the other with phase cycling. Peng et al 71 demonstrated that a new complexvalued curve-fitting model could solve the issue of T 1 contamination and acquisition time could be reduced.…”
Section: Updates On Improved Rf Pulse Sequences and Sequence Optimiza...mentioning
confidence: 99%
“…In the first two sequences, where Mz reset is used, the SE can be described as 39 : Mxy(n)goodbreak=A(n)Mprepgoodbreak+B(n),$$ {M}_{xy}(n)=A(n){M}_{\mathrm{prep}}+B(n), $$ where 1nitalicVPS$$ 1\le n\le VPS $$, and A(n)goodbreak=eτtrue[]i=1n1e1cos()αi10.25emif0.25emn=1e2sin()αn,$$ A(n)={e}_{\tau}\overset{1\ \mathrm{if}\ n=1}{\overbrace{\left[\prod \limits_{i=1}^{n-1}{e}_1\cos \left({\alpha}_i\right)\right]}}{e}_2\sin \left({\alpha}_n\right), $$ alignleftalign-2Bfalse(nfalse)=M01eτtruei=1n1e1cosαi1ifn=1align-1align-2+1e1true1+p=2n1i=pn1e1cos...…”
Section: Methodsmentioning
confidence: 99%